Accuracy of Shukla’s formula for depth of insertion of umbilical venous catheter - Vegesna Dedeepya; Gudavalli Mounica; N. L. Sravanthi; Arigela Sumasree; B. Vijaya Lakshmi (International Journal of Contemporary Pediatrics, 2023)
Background: The use of umbilical venous catheter (UVC) is an essential part of neonatal care allowing delivery of intravenous fluids, nutrition, and medication. It is important to know the position of the UVC tip accurately at the first attempt to prevent complications and minimize handling. We aimed to determine the precision and accuracy of Shukla’s formula developed to guide UVC placement and to evaluate the probability of UVC placement at desired radiological markings using weight-based Shukla’s formula. Methods: This study was carried out at NICU in NRI medical college, a tertiary care center in Chinakakani, Andhra Pradesh, India. A prospective observational study was done from December of 2021 to September 2022. With an aim to study the accuracy of Shukla’s formula in assessing the depth of insertion of UVC, depth was calculated and position of the tip of the catheter confirmed by x-ray. Results: We have taken 138 neonates in our NICU unit with mean gestational age of 33.91 wks. and with mean birth weight of 1.91 kg. Out of 138 infants 99 had a successful ideal UVC placement using Shukla’s formula. In reference to gestational age out 83 newborns in gestational age between 32-36 weeks 62 had ideal placement of UVC. In reference to birth weight ideal position of the UVC was seen in 73% of newborns. Conclusions: Shukla’s formula provided a reasonably accurate probability of achieving ideal UVC position in most of our babies: accurate in 72%.